(untitled) (American Journal of Islam and Society, 2011)
In Search of the Sacred, as the subtitle indicates, lets readers in on a wideranging conversation between Seyyed Hossein Nasr, one of the world’s most prolific Muslim intellectuals, and his cousin, Ramin Jahanbegloo, about Nasr’s life and thought. Terry Moore provides a fine, admirably concise introduction, which, like many introductions to Nasr’s thought, occasionally borders on the hagiographic. Those who are relatively unfamiliar with Nasr’s life, let alone his thought, will learn a lot from this highly readable book and, hopefully, be inspired to read some, or more, of his prodigious oeuvre. It would be of particular interest to students of Islam, comparative religion, religious studies, philosophy of religion, political philosophy and theory, and traditional studies. Those who are familiar with Nasr’s work, meanwhile, may not learn much that is new here, although they may gain a different perspective or new insights on certain aspects of Nasr’s thought. At times, it feels as though you are sitting in the same room as Nasr and Jahanbegloo, which is certainly a treat ...